2018
DOI: 10.1016/j.cellsig.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Cellular phosphatase activity of C1-Ten/Tensin2 is controlled by Phosphatidylinositol-3,4,5-triphosphate binding through the C1-Ten/Tensin2 SH2 domain

Abstract: Regulation of tyrosine phosphorylation on insulin receptor substrate-1 (IRS-1) is essential for insulin signaling. The protein tyrosine phosphatase (PTP) C1-Ten/Tensin2 has been implicated in the regulation of IRS-1, but the molecular basis of this dephosphorylation is not fully understood. Here, we demonstrate that the cellular phosphatase activity of C1-Ten/Tensin2 on IRS-1 is mediated by the binding of the C1-Ten/Tensin2 Src-homology 2 (SH2) domain to phosphatidylinositol-3,4,5-trisphosphate (PtdIns(3,4,5)P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
(73 reference statements)
1
12
0
Order By: Relevance
“…Tensin‐2 retains the cysteine residue, but lost the histidine and arginine residues. There is evidence that tensin‐2 might be catalytically active, as it was shown to bind to PI(3,4,5)P 3 , which was shown to increase its ability to dephosphorylate IRS1 and to regulate insulin receptor signaling [144,145]. Thus, tensin‐2 is potentially a catalytically active pseudophosphatase.…”
Section: Pseudoenzymes Within the Cc1‐fold Phosphatase Familymentioning
confidence: 99%
“…Tensin‐2 retains the cysteine residue, but lost the histidine and arginine residues. There is evidence that tensin‐2 might be catalytically active, as it was shown to bind to PI(3,4,5)P 3 , which was shown to increase its ability to dephosphorylate IRS1 and to regulate insulin receptor signaling [144,145]. Thus, tensin‐2 is potentially a catalytically active pseudophosphatase.…”
Section: Pseudoenzymes Within the Cc1‐fold Phosphatase Familymentioning
confidence: 99%
“…Based on the results of their previous systematic study on SH2 domain lipid binding, Kim et al have investigated C1-Ten/Tensin2 [ 53 ]. This protein is highly similar in amino acid sequence and domain organization to Tensin [ 54 ].…”
Section: Many Sh2 Domains Themselves Browse Membrane Lipids Besides Tyrosine Phosphorylated Proteins To Find the Matching Partnersmentioning
confidence: 99%
“…It preferentially dephosphorylates Y612 of IRS-1, which is associated with accelerated IRS-1 degradation. In their study, Kim et al found that C1-Ten/Tensin2 attenuates IRS-1 phosphorylation in a PI3K-dependent manner [ 53 ]. Structural analyses of the C1-Ten/Tensin2 SH2 domain have suggested that it also possesses a distinct cationic patch formed by K1147, K1155, and K1157, which is far from the pY-binding pocket.…”
Section: Many Sh2 Domains Themselves Browse Membrane Lipids Besides Tyrosine Phosphorylated Proteins To Find the Matching Partnersmentioning
confidence: 99%
See 1 more Smart Citation
“…has also been reported to influence the phosphorylation of IRS-1 (insulin receptor substrate 1) via binding to phosphatidylinositol-3,4,5-triphosphate, therefore contributing to the regulation of insulin signalling pathways (Kim et al, 2018). (Hong et al, 2016).…”
Section: Tensinmentioning
confidence: 99%